Effect of Escherichia coli Heat-Stable Enterotoxin on Cyclic GMP Levels in Mouse Intestine - Newsome, P.M. (1978)
Partially purified heat-stable enterotoxin obtained from Escherichia coli strain F11/P155 caused an accumulation of cyclic GMP in the intestines of 8-day-old mice.